Autoeficacia y manejo del estrés en estudiantes de la Unidad Educativa “Aguirre Abad” del Recinto Pisagua Alto del cantón Montalvo - Aráuz Cedeño, Doménica Mercedes (2025)
This research analyzes the relationship between self-efficacy and stress management in students at the "Aguirre Abad" Educational Unit in the Pisagua Alto area, Montalvo canton. The aim is to determine how self-efficacy influences students' ability to manage academic stress. The research is relevant because poorly managed stress and low self-efficacy can affect students' academic performance and mental health. A descriptive design with a quantitative approach and qualitative techniques was used. Data was collected using the General Self-Efficacy Scale by Schwarzer and Baessler, and the Perceived Stress Scale (PSS) by Cohen, complemented with interviews and observations. The analysis of the results provides key insights for developing intervention programs that strengthen self-efficacy and improve stress coping strategies for students. The research provides valuable conclusions for Educational Psychology, focusing on addressing learning and emotional issues, and offers recommendations for educators and mental health professionals. Additionally, key psychological indicators for assessing self-efficacy were identified, such as confidence in one's abilities, perseverance through obstacles, and self- perception of competence. The impact of stress perception on self-efficacy was analyzed, revealing how high stress can reduce students' ability to cope with challenging situations. Students with high self-efficacy tend to be more resilient to stress, showing traits of self-education, efficient organization, and adaptability. This comprehensive approach highlights the importance of cultivating self-efficacy to improve students' ability to cope with stress and achieve academic and personal success, while also safeguarding their emotional well-being.